Infectious diseases, autoimmunity and midline defect in a patient with a novel bi-allelic mutation in IL12RB1 gene - Göktürk, Bahar; Reisli, İsmail and Çalışkan, Ümran and Oleaga-Quintas, Carmen and Deswarte, Caroline and Turul-Özgür, Tuba and Burgucu, Durmuş and Migaud, Melanie and Casanova, Jean-Laurent and Picard, Capucine and Bustamante, Jacinta (The Turkish Journal of Pediatrics, 2016)
Clinical disease caused by weakly pathogenic mycobacterial species, which is known as Mendelian susceptibility to mycobacterial disease (MSMD), is a rare entity. IFN-γ and IL-17 production are defective due to insufficient response to IL-2 and IL-23 in IL-12Rβ1 deficiency; so this also causes tendency to intracellular microorganisms and candidal diseases. Here, we present a patient who suffers IL-12Rβ1 deficiency caused by a novel bi-allelic mutation with recurrent salmonellosis, mycobacterial, fungal infections and remained asymptomatic during 13 months of follow-up after hIFN-γ treatment. In addition she had hemolytic anemia and midline defects like cleft lip and palate which have not been reported in a patient with MSMD in the literature prior to this case report. In conclusion, diagnosis of MSMD should be kept in mind in patients with recurrent salmonellosis, mycobacterial and fungal infections especially in countries with a high consanguinity rate.